Endoscopic retrograde appendicitis therapy versus laparoscopic appendectomy for uncomplicated acute appendicitis - Yang, Baohong; Kong, Lingjian; Ullah, Saif; Zhao, Lixia; Liu, Dan; Li, Deliang; Shi, Xuezhong; Jia, Xiaocan; Dalal, Paras; Liu, Bingrong (Endoscopy, 2022)
Background Endoscopic retrograde appendicitis therapy (ERAT) is a new and minimally invasive technique for the treatment of acute appendicitis. This study aimed to assess the efficacy and clinical outcomes of ERAT versus laparoscopic appendectomy for patients with uncomplicated acute appendicitis. Methods We adopted propensity score matching (1:1) to compare ERAT and laparoscopic appendectomy in patients with uncomplicated acute appendicitis between April 2017 and March 2020. We reviewed 2880 patients with suspected acute appendicitis, of whom 422 patients with uncomplicated acute appendicitis met the matching criteria (ERAT 79; laparoscopic appendectomy 343), yielding 78 pairs of patients.Results The rate of curative treatment within 1 year after ERAT was 92.1 % (95 % confidence interval [CI] 83.8 % to 96.3 %). The percentage of patients recording visual analog scale values of  ≤ 3 for pain at 6 hours after treatment was 94.7 % (95 %CI 87.2 % to 97.9 %) in the ERAT group, which was significantly higher than that in the laparoscopic appendectomy group (83.3 %; 95 %CI 73.5 % to 90.0 %). Median procedure time and median hospital length of stay were significantly lower in the ERAT group compared with the laparoscopic appendectomy group. At 1 year, the median recurrence time was 50 days (interquartile range 25–127) in the ERAT group. The overall adverse event rate was 24.4 % (95 %CI 14.8 % to 33.9 %) in the laparoscopic appendectomy group and 18.4 % (95 %CI 9.7 % to 27.1 %) in the ERAT group, with no significant difference between the two groups.Conclusion ERAT was a technically feasible method of treating uncomplicated acute appendicitis compared with laparoscopic appendectomy.